A tool to evaluate learning trajectories of length measurement with children 6-8 years (Edma 0-6: Educación Matemática en la Infancia, 2021)
This paper presents the design and construction of a tool for the characterization of learning trajectories of length measurement in 6-8 years old children. The process followed has allowed us to configure and validate an instrument that permits to recognize, through open and manipulative activities, levels of understanding of the measure of length, such as: pre-length quantity recognizer; length quantity recognizer; length direct comparer; indirect length comparer; serial orderer to 6+; end-to-end length measurer; length unit relater and repeater. The instrument provides different types of evidence for a better approach to children comprehensions, such as their actions, their explanations and their questions.
Keywords: Learning trajectories; Length measurement; Early years; Instrument design